Archives of authority : empire, culture, and the Cold War - Rubin, Andrew (Andrew N.) (Translation/transnation., 2012)
Combining literary, cultural, and political history, and based on extensive archival research, including previously unseen FBI and CIA documents, Archives of Authority argues that cultural politics--specifically America's often covert patronage of the arts--played a highly important role in the transfer of imperial authority from Britain to the United States during a critical period after World War II. Andrew Rubin argues that this transfer reshaped the postwar literary space and he shows how, during this time, new and efficient modes of cultural transmission, replication, and travel--such as radio and rapidly and globally circulated journals--completely transformed the position occupied by the postwar writer and the role of world literature.